GREEN ACCOUNTING BASED ON UNIVERSITY SOCIAL RESPONSIBILITY: UNDERSTANDING AND CONCERN IN APPLICATION - Novira Sartika; Muhammad Luhtfi Iznillah (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
Along with the development of the world today, every organization (including universities) is expected to be able to make a positive contribution to its social environment, namely through Corporate Social Responsibility (CSR) or in higher education called University Social Responsibility (USR) which is synergized in the Tri Dharma of Higher Education. This study aims to see the understanding and concern of the Bengkalis State Polytechnic regarding Green Accounting based on University Social Responsibility. This research is a mixed research, the quantitative approach is used with index analysis with the help of SPSS, while the qualitative approach is using interviews and focus group discussions. The population in this study was the entire academic community of the State Polytechnic of Bengkalis with purposive sampling technique. The results showed that the index scores on 4 aspects of Green Accounting, namely environmental awareness, environmental involvement, environmental reporting and environmental auditing were between 60% - 79.99% or categorized as good. Based on the results of interviews and FGDs, it is known that in general Polbeng understands and cares about the environment, although there is no specific policy regarding its implementation